Two major cuticular proteins are required for assembly of horizontal laminae and vertical pore canals in rigid cuticle of Tribolium castaneum - Noh, Mi Young; Kramer, Karl J.; Muthukrishnan, Subbaratnam; Kanost, Michael R.; Beeman, Richard W.; Arakane, Yasuyuki (My University, 2014)
The insect exoskeleton is composed of cuticle primarily formed from structural cuticular proteins (CPs) and the polysaccharide chitin. Two CPs, TcCPR27 and TcCPR18, are major proteins present in the elytron (highly sclerotized and pigmented modified forewing) as well as the pronotum (dorsal sclerite of the prothorax) and ventral abdominal cuticle of the red flour beetle, Tribolium castaneum. Both CPs belong to the CPR family, which includes proteins that have an amino acid sequence motif known as the Rebers & Riddiford (R&R) consensus sequence. Injection of double-stranded RNA (dsRNA) for TcCPR27 and TcCPR18 resulted in insects with shorter, wrinkled, warped and less rigid elytra than those from control insects. To gain a more comprehensive understanding of the roles of CPs in cuticle assembly, we analyzed for the precise localization of TcCPR27 and the ultrastructural architecture of cuticle in TcCPR27- and TcCPR18-deficient elytra. Transmission electron microscopic analysis combined with immunodetection using goldlabeled secondary antibody revealed that TcCPR27 is present in dorsal elytral procuticle both in the horizontal laminae and in vertical pore canals. dsRNA-mediated RNA interference (RNAi) of TcCPR27 resulted in abnormal electron-lucent laminae and pore canals in elytra except for the boundary between these two structures in which electron-dense molecule(s) apparently accumulated. Insects subjected to RNAi for TcCPR18 also had disorganized laminae and pore canals in the procuticle of elytra. Similar ultrastructural defects were also observed in other body wall regions with rigid cuticle such as the thorax and legs of adult T. castaneum. TcCPR27 and TcCPR18 are required for proper formation of the horizontal chitinous laminae and vertical pore canals that are critical for formation and stabilization of rigid adult cuticle.
Keywords: Tribolium castaneum; Cuticular protein; Elytron; RNA interference; Transmission electron microscopy; Pore canal